PENGARUH HARGA DINAMIS TERHADAP LOYALITAS PELANGGAN DALAM PLATFORM E-COMMERCE - Agus Wahyudi; Amelia Andhini Syaharani; Ellya Novita Devianti; Dinda Kumalasari; Naura Da Rachman (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the effect of dynamic pricing on customer loyalty in e-commerce platforms. Dynamic pricing is a flexible strategy that allows price changes based on factors such as demand, product availability, and consumer behavior, optimized through advanced technology. Although it provides a competitive advantage, the implementation of dynamic pricing presents challenges, especially related to consumers' perceptions of price fairness. This study uses qualitative methods through interviews and observations to explore consumers' perceptions, experiences, and views on this strategy. The results show that transparency and good communication in the implementation of dynamic pricing play an important role in building consumer trust. Price changes accompanied by real benefits, such as discounts, can increase customer loyalty, while ambiguity in price changes can reduce trust and encourage consumers to switch to other platforms. Therefore, dynamic pricing strategies need to be designed with attention to fairness and consumer satisfaction in order to maintain a positive long-term relationship with customers.